2018
DOI: 10.1097/md.0000000000011743
|View full text |Cite
|
Sign up to set email alerts
|

Association study of gut flora in Wilson's disease through high-throughput sequencing

Abstract: In this study, we analyzed the difference of intestinal flora polymorphisms between Wilson's disease (WD) patients and healthy people by high-throughput sequencing technology, and explored the correlation between WD and intestinal flora polymorphism.A total of 22 cases of WD patients and 22 healthy persons as control were recruited. The total DNA was extracted from the fecal specimens of all the subjects, V4 high variable region of 16S rRNA gene was amplified and sequenced by high-throughput sequencing. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
(23 reference statements)
5
18
0
Order By: Relevance
“…Gut microbiota comparison between autism spectrum disorder (ASD) and control groups at the species level. The species with significant richness difference (p < .05, computed by STAMP) between the two groups are shown Megamonas, a harmful bacteria related to Wilson's disease [Geng et al, 2018] and obesity [Kieler et al, 2017]. Similarly to that in previous reports, we also found a significant reduction in the proportion of four genera (Escherichia/Shigella [Strati et al, 2017], Dialister [F. Strati et al, 2017], Haemophilus [Kang et al, 2018], and Flavonifractor [Ma et al, 2019]) in ASD samples compared to in the control.…”
Section: Discussionsupporting
confidence: 87%
“…Gut microbiota comparison between autism spectrum disorder (ASD) and control groups at the species level. The species with significant richness difference (p < .05, computed by STAMP) between the two groups are shown Megamonas, a harmful bacteria related to Wilson's disease [Geng et al, 2018] and obesity [Kieler et al, 2017]. Similarly to that in previous reports, we also found a significant reduction in the proportion of four genera (Escherichia/Shigella [Strati et al, 2017], Dialister [F. Strati et al, 2017], Haemophilus [Kang et al, 2018], and Flavonifractor [Ma et al, 2019]) in ASD samples compared to in the control.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the decrease of these two probiotics probably contributes to the disorder of physiological functions as Firmicutes in WD patients. The gut microbiome in the WD group also showed a significantly higher abundances of Proteobacteria and Fusobacteria than healthy individuals, consistent with the results reported by Geng [11]. The opportunistic pathogen of Proteobacteria created a major structural imbalance of gut microbiota in WD patients, while Fusobacteria have been widely recognized for the potential inducer of T regulatory cells or carcinogens promoting autophagy activation [24].…”
Section: Discussionsupporting
confidence: 87%
“…This is the first study to elaborate the detailed feactures of diversity and composition of gut microbiome in WD and explored the possible microbiome-related functions, some results of which were different from the study performed by Geng [11]. Though the two studies both showed an elimination, decreased density and loss of bacterial diversity of the microbial ecosystem in the WD patients, however, some opponent characterizations of the gut microbiome in WD were discovered in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, depending on the status of microbiota, diverse numbers of aged neutrophils might be available in mice with subchronic copper deficiency and Atp7a mutants, while it is the aged neutrophil phenotype that exhibits enhanced NET formation under inflammatory conditions (70). Although we are unaware of studies on microbiota composition in Menkes disease-affected humans or mice, it is known to be altered in Wilson disease patients (72). Therefore, verification of microbiota changes in Menkes patients and in Wilson and Menkes mice could shed light on this issue.…”
Section: Discussionmentioning
confidence: 99%